Weakly compressible Lattice Boltzmann simulations of reacting flows with detailed thermo-chemical models. (1st January 2020) - Hosseini, S.A.; Eshghinejadfard, A.; Darabiha, N.; Thévenin, D.
Abstract: Given the complex geometries usually found in practical applications, the Lattice Boltzmann (LB) method is becoming increasingly attractive for flow simulations. In addition to the simple treatment of intricate geometrical configurations, LB solvers can be implemented on very large parallel clusters with excellent scalability. However, reacting flows lead to additional challenges and have seldom been studied by LB methods. In this study, an in-house low Mach number Lattice Boltzmann solver, ALBORZ, has been extended to take into account multiple chemical components and reactions. For this purpose, the temperature and species of each mass fraction field are modeled through separate distribution functions. The flow distribution function is assumed to be independent of temperature and species mass fractions, which is valid in the limit of weak density variations. In order to compute reaction terms as well as variable thermodynamic and transport properties, the LB code has been coupled to another library of our group, REGATH. In this manner, LB simulations with detailed chemical kinetics and thermo-chemical models become possible. Since the code is currently limited to weak density variation, its performance has been checked for a laminar premixed as well as non-premixed counter-flow Ozone/Air reacting flow, describing kinetics with 4 species and 18 elementary reactions. Comparisons of the obtained reacting flow structures with results from classical finite-difference simulations show excellent agreement.